Does long-term proteinuria alter the correlation between 24‑h urine protein and spot urine protein / creatinine ratio and have an impact on body composition? (Annals of Medical Research, 2021)
Aim: We aimed to evaluate the accuracy of the protein-to-creatinine ratio (PCR) and whether or not PCR could be used instead of 24-hour proteinuria in profound glomerular diseases. Additionally, we investigated the impact of proteinuria on body composition.Material and Methods: Fifty subjects were enrolled in the study. Twenty of the participants were patient and had been following for glomerular diseases. All patients had over 1500 mg proteinuria for the last 3 months which has been detected by 24 hours urine sample. Control group was selected from 30 healthy volunteers.Results: In the patients group, the correlation between the 24-hour proteinuria and the proteinuria obtained from the ratio of spot urine PCR was investigated and a statistically significant correlation was found between the two parameters (p = 0.000, r = 0.731). To reveal if there is the effect of proteinuria on body composition between the two groups, the body composition parameters were compared. There was no statistically significant difference between the two groups in terms of body composition parameters, such as fat mass (p=0.500), lean body mass (p=0.280), muscle mass (p=0.277).Conclusion: Determination of proteinuria by spot urine technique in profound glomerular diseases can be used safely instead of the 24-h measurement method. Another finding of our study is that glomerular diseases do not affect body components.Keywords: Glomerular diseases; body composition; protein/creatinine ratio; proteinuria.
Keywords: Glomerular diseases; body composition; protein/creatinine ratio; proteinuria.